Nietzsche y la razón poética (Reflexión sobre la postura nietzscheana en torno a la cuestión de la razón moderna) (Artículo) - Luis Antonio Velasco Guzmán (Nóesis)
This paper analyses the possibility that opens up Nietzsche's claim about the poetic reason as an independent and different knowledge against the one that is characterized with the canonical characteristics of the strong rationality (such as "system", "method", "clarity", etc.), and try to scrutinize its epistemological thesis. My approach of Nietzsche's poetic reason will be directed by my studies on Nietzsche's Also sprach Zarathustra [1883- 5], which hermeneutical axis I have obtained from Nietzsche's Ecce Homo [1888] and Morgenröthe [1882], but also being directed by the great books on this topic written by M. Heidegger, K. Jaspers and S. Rosen.